The Mobile Robot HILARE: Dynamic Modeling and Motion Simulation - M. Ghazal; A. Talezadeh; M. Taheri; M. Nazemi-Zade (Institute of Advanced Engineering and Science, 2015)
To perform mission in variant environment, several types of mobile robot has been developed an implemented. The mobile robot HILARE is a known wheeled mobile robot which has two fixed wheels and an off-entered orientable wheel. Due to extended application of this robot, its dynamic analysis has attracted a great deal of interests. This article investigates dynamic modeling and motion analysis of the mobile robot HILARE. As the wheels of the robot have kinematic constraints, the constraints of wheels are taken into consideration and the matrix form of the kinematic model of the robot is derived. Furthermore, dynamic model of the robot is developed by consideration of kinematic constraints. To derive dynamic equations of the robot, the Lagrange multiplier method is employed and the governing equations of the robot in state-pace form are presented. Then, some simulations are presented to show applicability of the proposed formulation for dynamic analysis of the mobile robot HILARE.